From Trash to Treasure: Turning Air Pollutants into Materials for Energy Storage. Issue 6 (4th April 2017) - Liang, Jiachen; Zhang, Chen; Liu, Donghai; Zhang, Lina; Ling, Guowei; Yang, Quan‐Hong
Abstract: Environmental and energy issues are hot topics in the sustainable development of our planet. Air pollution, as a vital environmental issue, has puzzled us for decades, and a green and economical approach to control air pollutants is urgently required. New energy‐storage techniques have emerged as fascinating routes to reduce potential environmental problems. Therefore, the combination of air pollutants with energy‐storage devices is an appealing solution for air pollution. Herein, the principles of recovering air pollutants for use in energy‐storage materials are proposed, including their direct use as active materials, their conversion into active materials, and their use as dopants to modify the electrode. Typical air pollutants are selected to demonstrate their potential use in green energy storage. Future prospects of the broad application of air pollutants in energy‐related fields are also commented on. Abstract : The energy crisis and air pollution, as crucial issues for sustainable development of our planet, have puzzled us for decades. Turning air pollutants into materials for energy storage is a promising way to solve the environmental and energy issues simultaneously.